Implementation of Strategic Human Resource Management in Improving the Quality of Education - Pradana, Yudhan; Arijanto, Agus (Indonesian Journal of Business Analytics, 2024)
This research was conducted at Labschool Cirendeu Middle School by analyzing Strategic HR Management as an effort to improve the quality of education at that school. Researchers use research strategy design. This research was qualitative research with the consideration that the problem and aim is to look at the phenomenon of the conditions of the implementation of Strategic HR. The data collection method used consisted of observation and questionnaires. Nvivo, the coding process is carried out by linking the text in the transcript with code. Strategic HR Management to improve the quality of education at that school which consists of seven themes, namely Quality Assurance, Quality Improvement, Planning and Evaluation, Supervision, Recruitment, Parents as partners, and Implemented Solutions.